MODEL PEMBELAJARAN EVERY ONE IS A TEACHER HERE DAN PENDEKATAN QUANTUM TEACHING UNTUK MENINGKATKAN KEMAM PUAN PEMECAHAN MAS ALAH MATEMATIS S ISWA S MP - Muntuan, Jade (Jurnal Padegogik, 2019)
Abstract: Based on the findings of previous studies, the Indonesian students’ mathematical problem solving skills were not high yet. This research used comparative design to find out whether the mathematical problem solving improvement of students who were taught using Everyone is a Teacher Here learning model and Quantum Teaching approach were significantly better than students who were taught using Everyone is a Teacher Here learning model only. The samples of this study were students from two classes of grade VII at SMP Negeri 5 Lembang, West Bandung. Students of class VII E were taught using Everyone is a Teacher Here learning model and VII C were taught using Everyone is a Teacher Here learning model with the Quantum Teaching approach. The improvement of students' mathematical problem-solving abilities who were taught using Everyone is a Teacher Here learning model and students who were taught using the Everyone is a Teacher Here model and the Quantum Teaching approach were categorized as “moderate”. Statistically, the students’ problem solving improvement of students who were taught using Everyone is a Teacher Here learning model and Quantum Teaching approach were significantly better than students who were taught using Everyone is a Teacher Here learning model only. The result of students' response to Everyone is a Teacher Here learning model were categorized as "neutral" and students' response to Quantum Teaching approach were categorized as “really like”. Keywords: Mathematical Problem Solving Skills, Everyone is a Teacher Here, Quantum Teaching.